Debt Limits in Fund Programs with Low-Income Countries. (Policy Papers; Policy Paper ;, 2013)
This annotated presentation on the debt limits policy (DLP) for Fund programs with low income countries (LICs) was discussed at an informal session of the IMF Executive Board on January 10, 2014. The presentation contains a proposed new approach to the handling of external borrowing limits in such programs, building on the analysis contained in an earlier paper, discussed by the IMF Board in March 2013. The January 10 Board discussion provided staff with suggestions on how to refine their proposals, but the Board did not take a position on the merits of the proposed approach. IMF staff are to present a formal proposal to modify the IMF's Debt Limits Policy (which covers all IMF lending programs, not merely those with low income countries) for consideration by the Fund's Executive Board in the coming months.